Management of Diabetic Ketoacidosis: Core Role of Nurses – A Comprehensive Review - Samar Abdullah Bosana et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Diabetic ketoacidosis (DKA) is a life-threatening acute complication of diabetes mellitus characterized by hyperglycemia, ketonemia, and metabolic acidosis. Its management requires rapid intervention and a multidisciplinary approach, where nurses play a pivotal role. This review focuses on the pathophysiology, clinical management, and critical role of nursing in DKA care. It emphasizes the importance of monitoring, patient education, and early intervention to improve outcomes. The integration of evidence-based practices into nursing care for DKA is discussed, along with recommendations for training and protocols to enhance nursing performance. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/249 https://doi.org/10.5281/zenodo.14251202